STIMULATION OF TERRITORIAL IDENTITY AND PROMOTION OF THE TERRITORY’S BRANDS - Timofeev, M.Yu. (Perm Federal Research Centre Journal, 2015)
This article focuses on the connection between of the promotion of the territory’s brands and the local community’s identity. Particular emphasis is put on the practice of revision of the factory territorial identity and also on the creation of the postindustrial territory’s image.